Barriers to uptake of RTS, S malaria vaccine in a malaria endemic area of western Kenya - Okanda, Irine; Okuto, Erick; Kwach, Timon; Omolo, Mevice; Abuonji, Emily; Seda, John; Ayodo, George (Research Square, 2024)
Globally in 2021, there were an estimated 247 million malaria cases in 85 malaria-endemic countries which accounted for over 619,000 deaths worldwide. An estimated 27 million malaria cases and 12,600 deaths attributed to malaria in Kenya in the year 2020 (1). In every 1000 live births, 84 die before attaining 5 years in Kenya (12). Despite the implementation of several malaria prevention measures, malaria infection is still high in Kenya with children under the age of 5 being most vulnerable. As a complimentary to the existing malaria prevention measured, there is a malaria vaccine for children under 5 years of age. However, there is a low uptake, especially the 3rd and 4th doses with limited information on the reasons for the low uptake. This study aimed at identifying reasons for the low uptake of RTS, S malaria vaccine in Muhoroni sub-county Kenya. Methods: Study design: The study employed an exploratory study design. A purposeful sampling method was used to select participants for focus group discussions (FGDs) and key informant interviews (KIIs). Four FGDs were conducted, 3 of them involved 25 parent/guardian whose children either completed or didn’t complete the recommended 4 doses or didn’t receive the vaccine at all, and 1 FGD involved 11 community health volunteers (CHVs). The KII involved 11 nurses in charge of maternal and child health (MCH) clinics. FGDs and KIIs guides were used for data collection. Data was analyzed thematically using NVIVO version 12. Results: The gaps in malaria vaccine implementation are inadequate knowledge about the vaccine to both parents/guardians and nurses, vaccine side effects and high number of doses. Others are the poor attitude of health care providers, vaccine unavailability, understaffing of the health providers resulting in long waiting times, and migration to non-implementing sub-counties. Conclusion: Barriers for malaria vaccine uptake were: Inadequate knowledge about the vaccine, vaccine side effects and number of doses, poor attitude of health care providers, migrations, vaccine unavailability, long waiting queue due to staff understaffing, economic activities, cultural beliefs and inadequate trainings of nurses.
Keywords: RTS, S Malaria Vaccine